Influence of Service Waiting Time and Service Quality on Patient Satisfaction and Its Impact on Patient Loyalty: A Case Study at the Pediatric Polyclinic: JEL Classification: I10, I11, L83, C38, M31 - Sari, Primadiati Nickyta; Ichsan, Burhannudin; Isa, Muzakar (Journal La Bisecoman, 2025)
Patient satisfaction serves as a critical indicator in evaluating the quality of healthcare service delivery. This study stems from concerns regarding extended waiting times experienced by patients at the Pediatric Polyclinic of Indriati Hospital Boyolali, which are believed to contribute to diminished satisfaction and loyalty among service users. The primary objective of this research is to assess and map the influence of service waiting time and service quality on patient satisfaction, as well as to examine the subsequent impact on patient loyalty toward the healthcare institution. A quantitative research approach was employed using a survey method, with data analyzed through causal statistical techniques utilizing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were collected via a convenience sampling method, involving 100 respondents who were currently receiving or had recently received services at the Pediatric Polyclinic of Indriati Hospital Boyolali. The findings reveal that both service waiting time and service quality have a significant and positive impact on patient satisfaction. Furthermore, these two variables also directly affect patient loyalty. Importantly, patient satisfaction was found to act as a significant mediating variable, bridging the influence of service waiting time and service quality on loyalty. These results underscore the necessity of enhancing service process efficiency and improving the quality of service interactions as key strategies for building trust and fostering long-term loyalty among hospital service users.